Recombination Dynamics Divergent of the RGD Region of Penton, Hexon and Fiber Genes for Adenovirus - Jawa, Basem (Journal of King Abdulaziz University: Medical Sciences, 2024)
Most recent adenovirus research has focused on using the virus as a vector, with limited attention paid to its evolution and genome stability. Traditional serological typing methods are insufficient for adenoviruses, leading to the use of sequencing limited regions of hexon and fiber genes. However, multiple recombination events have been identified within the adenovirus genome, suggesting that this limited typing approach may be unreliable. This study sequenced the penton gene of nine adenoviruses with previously agreed-upon hexon and fiber types. Six of these isolates exhibited a penton type different from their hexon and fiber types, indicating recombination between different viral types. Additionally, four of these six isolates had penton sequences with significant divergence from known adenovirus types. Further analysis revealed potential recombination events within the penton gene itself, between the hypervariable region the RGD loop. These findings highlight the prevalence of recombination in species D adenoviruses, not only between hexon and fiber genes but also between penton and hexon/fiber genes. Furthermore, intra-penton recombination events are common. This emphasizes the limitations of limited hexon/fiber typing and underscores the need for full genome sequencing for accurate adenovirus typing. These considerations are crucial for the development of adenovirus-based vectors.